First Report of Susceptibility Status of the Invasive Vector: Aedes albopictus to insecticides used in vector control in Morocco - Aboulfadl, Souhail; Mellouki, Fouad; Ameur, Btissam; Faraj, Chafika (Archives of Clinical and Biomedical Research, 2023)
Aedes albopictus has been newly recorded in Agdal district in Rabat in Morocco. Not only could the establishment of this species affect public health through epidemics but it also a nuisance in urban and sub-urban areas. Vector control is monitored by environmental actions and practices but chemical insecticides can be used to reduce adult mosquito densities during peak periods. However, the level of susceptibility of this mosquito to insecticides has not been studied yet in Morocco. This paper reports the results of the first study conducted to monitor the insecticide resistance of adult and larva Ae. albopictus to the insecticides currently used in the vector control. The study was carried out during May-June 2018 at Rabat from the north-west of the country. Adult susceptibility tests were performed following the WHO test procedures. One organochlorate (DDT 4%), one pyrethroids (cyfluthrin 0.15%), one carbamate (bendiocarb 0.1%) and one organophosphate (fenithrothion 1%) were tested at diagnostic doses (DD). The five-fold DD of bendiocarb were also used to yield information on the intensity of mosquito adult resistance. The results of the performed susceptibility bioassay showed that the vector is susceptible to cyfluthrin and resistant to DDT, bendiocarb and fenithrothion. Larval bioassays to temephos were conducted according to WHO standard operating protocol to establish the dose-mortality relationship and deduct the LC50 and LC90 then resistance ratios. We show that larval populations of Ae. albopictus are still sensible to this insecticide. This information could help policymakers to plan insecticide resistance management.